Different Flushing Frequency on Blood Metabolites Profile of Ewes and Their Lambs at Pre-Weaning Period - Fassah, Dilla Mareistia; Taniasari, Mila; Daeli, Fanny Rahmasari; Diapari, Didid; Astuti, Dewi Apri; Khotijah, Lilis (Buletin Peternakan, 2024)
This study determined the effects of different flushing frequency on performance and blood metabolite profile of ewes and their suckling lambs at pre-weaning period. Twelve multiparous Garut ewes (2 years-old, BW 30.06 ± 6.20 kg) and 18 lambs born to experimental ewes (lambing weight 2.49 ± 0.56 kg) were used in this study. Ewes were randomly assigned into four treatment groups in a complete block design, namely: without flushing (T0: control), flushing at the beginning of mating (T1: 2 weeks before and after mating), two times flushing (T2: T1 + 4 weeks flushing at mid-gestation), and three times flushing (T3: T2 + 2 weeks flushing at before and after parturition). Three times flushing increased ((p<0.05) the crude fat intake, while different flushing frequencies did not affect (p>0.05) dry matter intake and intakes of crude protein, crude fiber, nitrogen-free extract, and total digestible nutrients of ewes at the pre-weaning period. Different flushing frequencies did not change (p>0.05) the productive performances of ewes during the pre-weaning period. Flushing application improved (p<0.05) the average daily gain of pre-weaning lambs at 14 days, but it did not affect the weaning weight of lambs. Two times flushing showed no pre-weaning mortality rate (p<0.05). Flushing application tended to decrease (p=0.08) blood plasma triglyceride of ewes at 21- days, while two times flushing frequency tended to increase blood plasma cholesterol (p=0.05) and triglyceride (p=0.08) of lambs at 21 days. In conclusion, increased flushing frequency supports ewes and their twin lamb growth performance and blood metabolite profile at the pre-weaning period